Optimizing Raw Material Inventory Control for Aluminum Wardrobes Using the Material Requirements Planning (MRP) Method: A Case Study on Amal Jaya SME - Safutra, Nur Ihwan; Fole, Asrul; Dahlan, Muhammad; Hafid, Muhammad Fachry; Ahmad, Arfandi; Herdianzah, Yan; Muhtada, Ahmad (TALENTA Publisher, 2024)
This study aims to analyze the implementation of Material Requirement Planning (MRP) method in controlling raw material inventory for aluminum wardrobe production in Amal Jaya SME. The inability to accurately predict the average number of customer orders each month indicates unfulfilled consumer demand. Therefore, effective raw material control becomes crucial to ensure availability in accordance with demand. The objectives of this research are to evaluate the management of raw materials using the MRP method and identify its impact on cost efficiency of raw materials in the production process. Additionally, this study aims to optimize raw material inventory to maximize customer demand fulfillment. The MRP method was chosen as the primary approach in this research. The results of the analysis indicate that the implementation of MRP method with Lot for Lot (LFL) lot sizing is the most efficient choice in controlling raw material inventory. Based on calculations using lot-for-lot and Economic Order Quantity (EOQ) methods, the most efficient inventory expenditure incurred by the company amounts to Rp. 26,274,840. Thus, ordering raw materials with Lot for Lot lot sizing can be used as a solution to optimize the control of aluminum wardrobe inventory in Amal Jaya SME.